Pengaruh Model Pembelajaran Group Investigation Berbasis Alat Peraga Terhadap Hasil Belajar Matematika Ditinjau Dari Penalaran Matematika Pada Siswa Kelas VII Di SMP N 2 Sawit Boyolali - Selfy, Selfy; , Dra. Nining Setyaningsih, M.Si (2017)
This study aims to: (1) analyze and test support learning with group investigation model props based for learning outcomes math, (2) analyze and test support math reasoning for learning outcomes math, (3) analyze and test the interaction between learning models and math reasoning for learning outcomes math. Populations of this study were all students of class SMP N 2 Sawit Boyolali amounting to 130 students, while the samples is VIIB and VIIE class drawn by cluster random sampling technique. VIIB class amounting to 22 students as experiment group and VIIE class as control group. Before samples be given treatment a test balance do. The collection was conducted by documentation, questionnare and test. Data analysis technique used is two way analysis of different cells previously performed data analysis prerequisite normality test and homogenity test. Research result: (1) there is support learning with group investigation model props based for learning outcomes math, with FA = 12,54 (2) there is support math reasoning for learning outcomes math, with FB = 32,79 (3) there is interaction between learning models and math reasoning for learning outcomes math, with FAB =7,94.